SHAPING YOUNG LEARNERS’ CHARACTER THROUGH TEACHER QUESTIONING IN ENGLISH CLASSROOM ACTIVITIES - Mike Nurmalia Sari (Pendekar: Jurnal Pendidikan Berkarakter, 2021)
Abstrak: Artikel ini memberikan gagasan tentang pentingnya pembentukan karakter bagi siswa, terutama bagi pelajar muda. Orang menyadari bahwa pembentukan karakter baik seseorang dimulai sejak usia dini. Banyak cara yang harus dilakukan untuk membentuk karakter khususnya bagi anak didik, salah satunya melalui tanya jawab guru dalam kegiatan kelas bahasa Inggris. Kegiatan tersebut dapat diterapkan pada siswa sekolah dasar, dan hasilnya diharapkan karakter siswa menjadi lebih baik dengan menunjukkan kemampuannya dalam menjawab pertanyaan dengan lebih sopan, bertanya kepada guru secara bergiliran, dan menghargai pendapat orang lain.Abstract:  This article provides ideas on the importance of character building for students, especially for the young learners. People realize that shaping good character of somebody is started at the early stage of the age. Many ways shall be done to shape character especially for young learners, one of them is through teacher questioning in English classroom activities. The activities can be applied to the elementary school students, and the result is expected the students’ characters become better by showing their ability in answering questions more polite, asking the teachers in turns, and respect opinions of other people.